Prevalence of HDV infection in people living with HIV: Data from a multicenter Italian cohort - Nicolini, Laura Ambra; Menzaghi, Barbara; Ricci, Elena; Pontali, Emanuele; Cenderello, Giovanni; Orofino, Giancarlo; Cascio, Antonio; Pellicanò, Giovanni Francesco; Valsecchi, Laura; Molteni, Chiara; Vichi, Francesca; Bonfanti, Paolo; et al. (Frontiers in Medicine, 2023)
Objectives The development of novel antiviral agents active against Hepatitis Delta Virus (HDV) might change the natural history of chronic infection, reducing the risk for end-stage liver disease. People living with HIV (PWH) are at risk for bloodborne pathogens infection, but limited data on epidemiology of HDV infection is available in this setting. The aim of this study was to investigate HDV prevalence and attitude toward HDV testing and treatment in infectious diseases centers. Methods A cross sectional survey was performed among centers participating in the CISAI (Coordinamento Italiano per lo Studio dell’Allergia in Infezione da HIV) Group. The survey addressed anti-HDV prevalence and HDV-RNA detectability rates in PWH as well as perceived obstacles to treatment. Results Overall, responses from ten sites were collected. Among participating centers, 316 PWH with HBV chronic infection are currently followed. Of them, 15.2% had positive anti-HDV antibodies, while 13.9% were not tested yet. Overall, 17% of anti-HDV positive PWH tested at least once for HDV-RNA had active HDV infection, and 71% of them had advanced liver disease. Most infectious diseases centers intend to treat locally HDV infection with upcoming anti-HDV drugs, but some concerns exist regarding treatment schedule. Discussion HDV testing needs to be implemented in PWH. At present, few patients followed in the CISAI centers seem to be candidate to receive new direct active anti-HDV agents, but repeated HDV-RNA measures could change this proportion.